2020
DOI: 10.1186/s12885-020-07341-y
|View full text |Cite
|
Sign up to set email alerts
|

A predictive nomogram for lymph node metastasis of incidental gallbladder cancer: a SEER population-based study

Abstract: Background: Existing imaging techniques have a low ability to detect lymph node metastasis (LNM) of gallbladder cancer (GBC). Gallbladder removal by laparoscopic cholecystectomy can provide pathological information regarding the tumor itself for incidental gallbladder cancer (IGBC). The purpose of this study was to identify the risk factors associated with LNM of IGBC and to establish a nomogram to improve the ability to predict the risk of LNM for IGBC. Methods: A total of 796 patients diagnosed with stage T1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…e 1-year survival rates of the 2 groups were 91.43% vs. 76.71%, and the 2-year survival rates were 26.29% vs. 17.53%, respectively. It is well known that GBC patients with lymph node metastasis and nerve invasion have a more poor prognosis than those without [23,24]. Also, in this study, we found the same conclusion.…”
Section: Discussionsupporting
confidence: 87%
“…e 1-year survival rates of the 2 groups were 91.43% vs. 76.71%, and the 2-year survival rates were 26.29% vs. 17.53%, respectively. It is well known that GBC patients with lymph node metastasis and nerve invasion have a more poor prognosis than those without [23,24]. Also, in this study, we found the same conclusion.…”
Section: Discussionsupporting
confidence: 87%
“…Nomograms can also present simple statistical analysis and visualization results, which are helpful for clinical decisionmaking and for promoting the development of personalized medical therapy. Recently, nomograms have been broadly applied to predict the risk of LNM in different tumors and have been proven to be effective (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Our results of homogeneous CNV and driver mutation between primary tumor and LNM imply early metastasis with the evidences of. Recent evidence suggested metastasis could occur at early stage [36,53] and even 7% T1a tumor may have concomitant LNM [54]. Both indicate further analyses to generate robust data for this hypothesis.…”
Section: Discussionmentioning
confidence: 92%